2017
DOI: 10.1080/13651501.2017.1306081
|View full text |Cite
|
Sign up to set email alerts
|

Association between psychological measures with inflammatory anddisease-related markers of inflammatory bowel disease

Abstract: Active IBD is associated with symptoms of depression and anxiety and with a raised circulating inflammatory mediator profile. Patients with active IBD exhibiting psychological symptoms should undergo psychological evaluation to ensure the psychological aspects of the condition are considered and addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
1
29
0
2
Order By: Relevance
“…The Canadian IBD cohort study suggested that patients had higher lifetime prevalence rates of generalized anxiety disorder (GAD) and major depressive disorder (MDD) than the general population at 13.4% and 27.2% [ 20 ]. This is consistent with similar results which were found in studies initiated in the USA [ 7 ], China [ 21 ], Italy [ 22 ], Ireland [ 23 ], and South Korea [ 24 ]. A systematic review that combined multiple clinical studies showed that IBD had 19.2% and 21.2% anxiety and 21.2% depression, almost twice the rate of the general population, and 66.4% anxious mood and 34.7% depression in IBD patients who were also active.…”
Section: Ibd and Depressionsupporting
confidence: 93%
“…The Canadian IBD cohort study suggested that patients had higher lifetime prevalence rates of generalized anxiety disorder (GAD) and major depressive disorder (MDD) than the general population at 13.4% and 27.2% [ 20 ]. This is consistent with similar results which were found in studies initiated in the USA [ 7 ], China [ 21 ], Italy [ 22 ], Ireland [ 23 ], and South Korea [ 24 ]. A systematic review that combined multiple clinical studies showed that IBD had 19.2% and 21.2% anxiety and 21.2% depression, almost twice the rate of the general population, and 66.4% anxious mood and 34.7% depression in IBD patients who were also active.…”
Section: Ibd and Depressionsupporting
confidence: 93%
“…However, the evidence specifically testing inflammation as a correlate of depressive symptoms in patients with IBD is very limited. In a cross‐sectional study of 11 IBD patients and nine controls, symptomatic IBD patients had the highest depressive and anxiety scores, as well as increased intestinal expression of IL‐6 and IL‐1β and serum IL‐6 . Prospective studies testing the directionality of inflammation and depressive symptoms in IBD are awaited.…”
Section: Inflammation As a Link Between Depression And Ibdmentioning
confidence: 99%
“…Stepped care treatment model according to NICE guidelines [5] Criteria Mild or subthreshold depression For at least 2 weeks (or less if symptoms are severe and of rapid onset), the following 2 core symptoms present Group physical activity programme, group-based peer support or to low-intensity psychologi- of depressive symptoms in patients with IBD is very limited. In a cross-sectional study of 11 IBD patients and nine controls, symptomatic IBD patients had the highest depressive and anxiety scores, as well as increased intestinal expression of IL-6 and IL-1β and serum IL-6 [42]. Prospective studies testing the directionality of inflammation and depressive symptoms in IBD are awaited.…”
Section: Classification Of Diseases 10th Edition (Icd-10)mentioning
confidence: 99%
“…The close relation between anxious-depressive symptoms and IBD is presently explained in the emerging theories of “gut-brain axis” dysfunction ( 51 , 52 ). The presence of an alteration of the immune system in pro-inflammatory sense involves an alteration of the micro-anatomy and the gut microbiota ( 53 ), promoting the development of a neuro-inflammation, with a modification of synaptic plasticity and neuronal functioning ( 54 , 55 ). Overall, findings seem to confirm data emerging from a recent meta-analysis showing correlation between depressive symptoms and the negative progression of the disease, particularly in CD patients, who are more likely to suffer from depression compared with UC patients ( 56 ).…”
Section: Discussionmentioning
confidence: 99%